Novice ESL instructors' metacognitive awareness in teaching English / Rodhiah Hj Amzah - Hj Amzah, Rodhiah (2014)
Metacognition serves as an indicator of successful learning. Various researches have proven the association between academic success and also metacognition. This quantitative study attempted to investigate the Novice ESL Instructors Metacognitive Awareness in Teaching English. Besides that, this study aimed to identify the preferred aspect in both metacognitive knowledge and metacognitive regulation used by the instructors in teaching. Lastly, this study aimed to find if the significant relationship between the novice ESL instructors’ years of teaching with their metacognitive awareness in knowledge and regulation in teaching English. Novice instructors that are able to measure their awareness in teaching will have better control in the learning process. It will help them to know their strengths and weaknesses in teaching. It is found that novice ESL Instructors faced problems in teaching English due to lack of experience. Thus, it demotivates them and somehow affects their teaching performance. The Metacognitive Awareness Inventory for Teachers (MAIT) measures two aspects in metacognition; metacognitive knowledge and metacognitive regulation were administered to 100 novice ESL instructors from different types of educational institution in Malaysia. The data was then processed using the Statistical Packages for Social Sciences (SPSS) for Window version 20.0. The results supported the objective of this study that English instructors who are aware of their teaching process will have a better control in the learning process. Besides that, the result also found that there is no significant relationship between the respondents’ teaching experience and their metacognitive awareness in teaching. It is hoped that this study will provide better understanding in the study of metacognition that will improve the instructors’ belief in teaching and their also their teaching skills. In conclusion, English instructors with high metacognition in teaching can help to provide a better English learning environment to the students as well as improving their own pedagogical development.